IMPLIKASI SANKSI ADMINISTRASI KUP TERHADAP KEBERLANJUTAN MANAJEMEN KEUANGAN PERUSAHAAN - Maharani, Sylvanna Zahira (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Tax compliance is the foundation of state revenue, yet (General Provisions and Tax Procedures) administrative sanctions are often an unavoidable consequence for companies. These sanctions, in the form of fines, interest, and penalties, directly impact cash flow, but their long-term implications for the sustainability of financial management are often overlooked. This study aims to conceptually analyze how KUP administrative sanctions affect the dimensions of sustainable financial management. The method used is a conceptual literature study, which identifies and formulates research variable dimensions based on an in-depth literature review. The result is a conceptual framework that maps the implications of sanctions not only on short-term liquidity but also on fiscal risk management, strategic planning, and the company's investment reputation. In conclusion, administrative sanctions are not just a cost burden, but a strategic risk variable that must be integrated into sustainable financial management models to ensure long-term business viability.